Human Leukocyte Antigen (HLA) DQ2 and DQ8 Haplotypes in Children with Celiac Disease - Shamraiz, Ifnan; Naz, Shaista; Idrees, Saba; Ikram, Farooq; Khan, Husna; Khan, Samina (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of human leukocyte antigen-DQ2 and -DQ8 haplotypes in children with celiac disease in a tertiary care hospital. Study Design: Comparative cross-sectional study. Place and Duration of Study: Paediatric Gastroenterology and Hepatology Departments Combined Military Hospital, Rawalpindi Pakistan, from Feb 2022 to Feb 2023. Methodology: Diagnosed cases of celiac disease, from 1 to 15 years old, were selected as Cases (n=50), and an equal group of normal children of the same age as Control (n=50), were selected. Polymerase chain reaction for Human Leukocyte antigen (Human leukocyte antigen -DQ) genotyping was performed on all children. Results: The most frequently observed haplotype was DQ2, followed by DQ8. Among celiac patients, 94% tested positive for human leukocyte antigen-DQ, with 82% DQ2, 10% DQ8, and 2% DQ2/DQ8 positive. 6% were negative for any HLA-DQ allele, while only 8% were DQ2 positive in the control group. The frequency of human leukocyte antigen -DQ between the two groups was statistically significant (p-value<0.05). The association between anti-tissue transglutaminase antibody levels and human leukocyte antigen -DQ was also statistically significant (p-value<0.05). Biopsy findings and gender had no statistically significant association with human leukocyte antigen -DQ (p-value>0.05). Conclusion: Celiac disease has a varied spectrum of presentation, which often goes unrecognized by physicians. Therefore, genetic testing can be used as an additional diagnostic tool to reduce ambiguity and improve the accuracy of celiac disease diagnosis.